Metagenomic insights into isolable bacterial communities and antimicrobial resistance in airborne dust from pig farms - Hein, Si Thu; Prathan, Rangsiya; Srisanga, Songsak; Muenhor, Dudsadee; Wongsurawat, Thidathip; Jenjaroenpun, Piroon; Tummaruk, Padet; Chuanchuen, Rungtip (Frontiers in Veterinary Science, 2024)
This study aims to investigate bacterial communities and antimicrobial resistance (AMR) in airborne dust from pig farms. Airborne dust, pig feces and feed were collected from 9 pig farms in Thailand. Airborne dust samples were collected from upwind and downwind (25 meters from pig house), and inside (in the middle of the pig house) of the selected pig house.Pig feces and feed samples were individually collected from the pen floor and feed trough from the same pig house where airborne dust was collected. A direct total bacteria count on each sampling plate was conducted and averaged. The ESKAPE pathogens together with Escherichia coli, Salmonella, and Streptococcus were examined. A total of 175 bacterial isolates were collected and tested for MICs. Pooled bacteria from the inside airborne dust samples were analyzed using Metagenomic Sequencing. The highest bacterial concentration (1.9-11.2 × 10 3 CFU/m 3 ) was found inside pig houses. Staphylococcus (n = 37) and Enterococcus (n = 36) were most frequent bacterial species. Salmonella (n = 3) were exclusively isolated from feed and feces. Target bacteria showed a variety of resistance phenotypes, and the same bacterial species with the same resistance phenotype were found in airborne dust, feed and fecal from each farm. Metagenomic Sequencing analysis revealed 1,652 bacterial species across all pig farms, of which the predominant bacterial phylum was Bacillota. One hundred fifty-nine AMR genes of 12 different antibiotic classes were identified, with aminoglycoside resistance genes (24%) being the most prevalent. A total of 251 different plasmids were discovered, and the same plasmid was detected in multiple farms. In conclusion, the phenotypic and metagenomic results demonstrated that airborne dust from pig farms contained a diverse array of bacterial species and genes encoding resistance to a range of clinically important antimicrobial agents, indicating the significant role in the spread of AMR bacterial pathogens with potential hazards to human health. Policy measurements to address AMR in airborne dust from livestock farms are mandatory.